Pengaruh Kepemimpinan Kepala Desa Terhadap Pelaksanaan Pembangunan Desa (Studi Pada Kecamatan Arga Makmur Dan Kecamatan Arma Jaya) - Kasmanto , Bambang; Salamun, Salamun; Astuti , Linda; Rohati , Nely (Journal of Social Science and Humanities, 2024)
His study aims to examine the influence of the village head's leadership on the implementation of village development in Arga Makmur sub-district and Arma Jaya sub-district, North Bengkulu district. The data used is primary data obtained from distributing questionnaires to village heads in Arga, Makmur and Arma Jaya sub-districts, North Bengkulu Regency. The number of samples used in this study were 25 respondents. The data analysis used was simple linear regression analysis. Based on the results of the t test, the calculated t value is greater than t table (6.359 > 2.069) so the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. It can be concluded that there is a significant influence between the village head's leadership on the implementation of village development in Arga Makmur sub-district and Arma Jaya sub-district, North Bengkulu district.